Morfologi Tanaman Kedelai (Glycine max L. Merril) Akibat Pemberian Pupuk Kandang Kambing Dan Pupuk Urea - Situmeang, Ulfa Syahrina; Zulfida, Ida; Sibagariang, Edison (UNIVERSITAS LABUHANBATU, 2023)
Soybean plants (Glycine max L. merril) are the main source of vegetable protein for the majority of the Indonesian population. The Indonesian nation is one of the largest consumers of soybeans in the world. At least 2.4 million metric tons of soybeans per year are consumed by the Indonesian people. Based on a report from the Central Statistics Agency (BPS), the average national soybean productivity was 15.69 quintals per hectare (ku/ha) in 2020, and the level of dependence on Indonesian soybean imports in the last five years has reached 78.44% per year, with a trend of continuing increases annually (based on BPS 2020). Urea fertilizer is a chemical fertilizer that contains high levels of nitrogen (N). Nitrogen is an essential nutrient for plants (Tumewu et al., 2012). Urea-based fertilizer is water-soluble and absorbs water very easily (hygroscopic), so the nitrogen content in the soil is very low while the nitrogen content of plants is very important (Tumewu et al., 2012). This research was carried out in the practicum area of the agricultural faculty of the Indonesian Community Development University (UPMI), Jl. Balai Desa Pasar 12 Marindal II Medan Amplas. This research method uses a factorial randomized block design (RAK) with two factors studied, namely: Factor I: provision of 3 levels of goat manure (P), namely: A0: control (no goat manure), A1: 1 kg goat manure per plot, and A2: goat manure per kg/plot. Factor II: Urea Dose (U) consists of 3 levels, namely: U0: No Treatment/Control, U1: 50 kg/ha = 5 grams/plant; U2: 100 kg/ha = 10 grams/plant. Based on the results of direct field observations, it shows normal growth of soybean plants (Glycine max L. merril). Observation parameters include plant height (cm), number of productive branches, and number of pods. The single effect of giving goat manure at level A2 (2 kg goat manure per plot) has the effect of increasing plant height growth at the age of 3 WAP based on the 5% DMRT test. The interaction effect of giving goat manure (A) and giving a dose of urea fertilizer (U) had no effect on plant height, number of productive branches, or number of pods.